MAHAR DAN UANG PANAIK PERKAWINAN PADA TRADISI MASYARAKAT DALAM PANDANGAN HUKUM ISLAM (Studi Kasus di Kelurahan Limpomajang Kacamatan Marioriawa Kabupaten Soppeng) - Iqbal, Muhammad; L, Sudirman (Inspiratif Pendidikan, 2020)
This study aims to analyze the legal status in Islam regarding dowry and panaik money in Limpomajang Village, Marioriawa District, Soppeng Regency. In the process of collecting data, the writer used the method of observation and interviews with the village head, religious leaders, community leaders and youth leaders. In various sources found by the author, both the Quran, hadiths and the opinions of scholars, dowry is a gift that must be fulfilled and submitted by the prospective groom to the prospective bride, namely in the form of goods or services that have value and benefit, usually in the form of rings gold, rice fields, gardens and a set of prayer tools. Meanwhile, panaik money is the giving of a certain amount of money from the prospective groom to the prospective bride as a walimah fee. Dowry and Panaik money still exist and are used as conditions for marriage in Limpomajang Village, Marioriawa District, Soppeng Regency. Islamic law views that a dowry is a legal condition of marriage as the author finds in the Alquran and the Hadith of the Prophet. Meanwhile, panaik money is not found in various references to both the Quran and the Hadith of the Prophet, but only historical evidence so that it becomes a tradition and custom in society. It is known that religion forbids making it difficult for a marriage to take place, but panaik money is a heavy burden for men. Seeing the large amount of panaik money, it can bring harm or something bad for a marriage. So the authors conclude that panaik money is makruh and even haram when the method of obtaining panaik money is not in accordance with Islamic law.